The Significance of Antibodies against Domain I of Beta-2 Glycoprotein I in Antiphospholipid Syndrome - Kelchtermans, Hilde; Chayouâ, Walid; Laat, Bas de (Seminars in Thrombosis and Hemostasis, 2018)
The antiphospholipid syndrome (APS) is characterized by vascular thrombosis and/or pregnancy morbidity with the persistent presence of antiphospholipid antibodies (aPLs). Progress is being made in understanding the pathogenesis of the syndrome, but difficulties persist in the identification of patients at risk for thrombosis and/or pregnancy morbidity. Beta-2 glycoprotein I (β2GPI), a plasma protein consisting of five sushi domains, is thought to be the main antigenic target of aPLs. Antibodies recognizing domain I of β2GPI are predominantly present in patients with an elevated risk of thrombosis, whereas antidomain IV/V antibodies are found in nonthrombotic autoimmune diseases. Indeed, domain I antibodies proved to be pathogenic in multiple studies. Retrospective studies have provided evidence for an added clinical value of antidomain I antibodies in the risk stratification of patients with APS. Still, wide ranges of odds ratio exist between studies, probably due to differences in the study and control population, and detection methods used. Despite the proven pathogenicity of antidomain I antibodies and their correlations with clinical manifestations of APS, heterogeneity of the current studies has prohibited their acceptance in the official diagnostic criteria. Well-designed large longitudinal prospective studies with available and new, preferentially functional, assays for the risk stratification of patients with APS are required.
Keywords: antiphospholipid syndrome; β2 glycoprotein I; domain I antibodies